A mediação e sua aplicação no direito brasileiro - Lacerda Neto, Oswaldo Pacheco (2017)
The following dissertation aims at the utility of mediation by the Brazilian law. The laws over the subject, drawn up in a very recent past, are among the points of interest, as well as the tools that the Brazilian State created to make the mediation subject actually work, to the point of interfering positively in the judicial machine’s lubrication, battered by a culture that encourages rivalry, hostility and war. Therefore it is fundamental to examine the conflict and its links with psychology. The consequences of the conflict are also analyzed in order to identify appropriate mechanisms for their solution, aiming on the diffuse, collective and individual interests, public and private, widely and efficiently. The entire study is focused on conflict resolution in the context of the Democratic State of Law. The concept of mediation and its differences with the conciliation and arbitration are also addressed, as a way of analyzing ADR (alternative dispute resolution) modes and the social mediation as a mechanism of urban pacification. The means to facilitate the mediator in the pursuit of that peace, based on principles of psychology (as the rapport and the insight) are essential to the success of the procedure, but the true meaning is not the result of mediation settlement, but the perception of the righteous by the participants. The essence of mediation and the perception of “fair” go beyond the judicial process, (the traditional model of conflict resolution), so as to inflict conflicting parties to reflect on their opponent’s arguments. Consequently, the result reached by mediation is more capable of strengthen the society, in order to make peace, than the aggressiveness found in the traditional process, where the parties submit to the sovereign will of the judge. Thus, the concept of “law” accepted today lacks a closer relationship with the concept of “fair” as to recover the credibility of the judiciary and re-educate society in a direction opposite to that of the rivalry found in the traditional lawsuit model. The research method used here was the reading of bibliographic repertoire within the science of Laws, with strong contributions from the science of Psychology.